2002
DOI: 10.1136/jcp.55.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood gas samples produced by a pneumatic tube system

Abstract: Aims: To investigate the effect of a pneumatic tube system (PTS) on the results of samples sent for blood gas analysis to a central laboratory.Methods: Blood gas samples were analysed immediately or sent via the PTS to the laboratory for analysis. In addition, samples sent via the PTS in a pressure sealed container were compared with those sent non-pressure sealed to the laboratory. Results: Samples sent via the PTS had significant alterations in their pO 2 values, which were not seen when samples were carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 8 publications
1
21
0
3
Order By: Relevance
“…However, blood samples are particularly sensitive to strong forces or vibrations with high frequencies and require special attention. It has been shown that PTS transport could affect samples (7-9 ) and lead to hemolysis or altered blood gases (5 ). On the other hand, there are hospitals working with PTSs constructed in such a way that they do not affect samples or do so only minimally (1, 10 -12 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, blood samples are particularly sensitive to strong forces or vibrations with high frequencies and require special attention. It has been shown that PTS transport could affect samples (7-9 ) and lead to hemolysis or altered blood gases (5 ). On the other hand, there are hospitals working with PTSs constructed in such a way that they do not affect samples or do so only minimally (1, 10 -12 ).…”
Section: Resultsmentioning
confidence: 99%
“…The parameters were chosen with respect to literature on the evaluation of similar systems (4,5 ). We decided to analyze an expanded panel including differential blood count (LH 750, Beckman Coulter), coagulation tests (BCS XP, Siemens), erythrocyte sedimentation rate (S2000, Sarstedt), sodium, potassium, chloride, phosphate, glucose, magnesium, aspartate aminotransferase (ASAT), alanine aminotransferase (ALAT), lipase, LDH, troponin T, IgG, free thyroxine (Modular-System, Roche), procalcitonin (Kryptor, Brahms), and blood gas analysis (ABL 700, Radiometer).…”
Section: Analytesmentioning
confidence: 99%
“…In vitro hemolysis, caused by PTS, has been reported to alter the blood specimen's quality and potentially affects clinical laboratory measurements such as biochemical, most notably potassium (K), lactate dehydrogenase (LDH) [4], hematology and coagulation parameters. Moreover, these strong forces can potentially affect blood gas measurements [5] and spectrophotometric analysis of cerebrospinal fluid [6]. Most recently, the transportation of blood samples through the PTS has been shown to affect in vitro platelet function [7].…”
Section: Introductionmentioning
confidence: 99%
“…PTS induced pressure changes must be considered as a possible source for pre-analytical error for blood gas measurements. 4,5 Past investigations have observed that blood gases were not significantly altered when transported by PTS. [6][7][8] However, when an air bubble is present within a specimen transported via PTS, the P O 2 is significantly affected.…”
Section: Introductionmentioning
confidence: 99%